Tracing Mathematical Economics: Essays in the History of (Departments of) Economics - Cosendey, Matheus Assaf (2022)
This dissertation studies the history of the development of mathematical economics in the XX century through histories of economics departments. In the first chapter, we study how the small economics department at Stanford University became an important place for the development and expansion of mathematical economics in the United States since the interwar period, benefitting from cross-disciplinary connections which were particular to Stanfords institutional environment. In the postwar period, the rise of the behavioral sciences at Stanford allowed mathematical economics to bypass the limitations of the smaller department of economics, through the association with mathematics, statistics, and psychology. In the second chapter, we analyze how mathematical economics was able to find room at the department of economics at the University of California, Berkeley, despite the presence of an established economics tradition which mostly scorned the use of mathematics in the discipline. Despite the presence of some important mathematical economists in the university, such as Griffith Evans in the interwar period, and Robert Dorfman in the immediate postwar period, it was only by the end of the 1950s that mathematical economics could hold on its space in the department of economics, with the mobilization of university administration playing a central role in this process. Finally, the last chapter contributes to the history of the internationalization of mathematical economics to Brazil, by following the history of the Institute of Pure and Applied Mathematics (IMPA - Instituto de Matemática Pura e Aplicada). IMPA was created through the actions of the Brazilian mathematical community, but since its beginnings held some connections to economics. Although it began as an idiosyncratic connection through the young engineer turned economist Mário Henrique Simonsen, mathematical economics at IMPA rose to be considered an important part of applied mathematics research at the institute. Through this process of breaking fuzzy discipline borders, IMPA performed as a disseminator of the subject to Brazil and became an international actor within such intellectual community. By telling such different histories, the dissertation sheds light on the complex and multifaceted process of expansion and dissemination of mathematical economics in the XX century.